Vloga Ivana Molka v skupnosti ameriških Slovencev v Calumetu - Božič Horvat, Andreja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The purpose of this paper is to examine the life and work of Ivan Molek and his involvement in the American Slovenes community in Calumet. Ivan Molek was born on July 8, 1892 in parish Metlika. After he finished elementary school in Metlika he got a job in a government vineyard. In 1900 he immigrated to the USA and settled in Steelton (Pennsylvania) where he worked as a day laborer for the Pennsylvania Steel Company. Tired of constant tramping for work, he decided to leave Steelton and Pennsylvania. In spring 1903 he moved to the Michigan mining town of Calumet where some of his relatives already lived. In the beginning Molek stayed with his cousin's family and worked in a copper mine, but in May 1905 he was offered a job at the Glasnik Publishing Company. Molek became the editor of Glasnik, a local Slovene newspaper. While living and working in Calumet, Molek was exposed to socialist ideals through the pages of the weekly Appeal to Reason. When Molek moved to Chicago in 1906, at that time the center of political and cultural life of American Slovenes, his belief in socialist ideology was strengthen and he finally embraced democraticsocialism. He became an active member of the Slovene National Benefit Society and the Jugoslav Socialist Federation. He was a moderate socialist who promoted personal and social progress through enlightenment. According to him, social revolution meant constructive and positive progress in a process of peaceful development. Therefore he disagreed with militant policies and opposed violent revolution. He stressed the importance of democracy and individual freedom and fought hard against dictatorship of any kind - political, military, proletarian, religious, etc. As he rejected all dogmas, starting with religion, Molek came into conflict with many of the prevailing doctrinaire systems. Ivan Molek was also a prolific writer. He wrote in order to promote workers' rights and socialist ideology. In his writings, Molek constantly attacked hypocrisy, exploitation, corruption, insincerity, opportunism and similar vices. Molek produced works of fiction and non-fiction. His subject matter was politics, history, science, and religion. He had a special proclivity for satire, wit, and humor, which he most successfully used in his polemics.
Keywords: Molek, Ivan, 1882-1900; slovenski izseljenci; United States of America; ZDA; biografije